Penggunaan User Acceptance Testing (UAT) Pada Pengujian Sistem Informasi Pengelolaan Keuangan Dan Inventaris Barang - Aliyah Aliyah; Nahrun Hartono; Asrul Azhari Muin (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
Software testing is a crucial stage in the development of information systems to ensure that applications can function according to user needs. System feasibility testing using UAT is intended to ensure that the system meets the functional requirements specified by the users. This study aims to apply UAT to a financial and inventory management information system used to manage various operational needs of the company, such as inventory recording, expense and income reporting, and employee wages. The UAT process is conducted by the system’s end-users, consisting of 16 respondents, including employees and the owner of CV. Nitah Tirta Makassar. The testing methodology includes several stages: UAT planning, preparing test questions through a Google Forms (gforms) questionnaire, conducting the tests, and analyzing the test result calculations. The results of this study indicate that the financial and inventory management information system meets user needs, based on UAT questionnaire score calculations that achieved an average interpretation score above 87% with a "very good" rating. With the implementation of UAT, it can be concluded that the financial and inventory management information system meets the users' requirements.